92. Neurophysiology and ultrasound in diagnosis of isolated peripheral nerve tumors. Literature revision and personal experience. Issue 1 (January 2015) - Coraci, D.; Santilli, V.; Erra, C.; De Franco, P.; Padua, L.
<x xml:space="preserve">Abstract</x> Our work shows the association of neurophysiology and ultrasound in the assessment of peripheral nerve tumors. In these cases, neurophysiologic examination presents an important role to define the possible lack of function of the nerve. Ultrasonography allows us to visualize the peripheral nerves and underline the morphologic changes in nerve structure. We present a literature revision about ultrasound in peripheral nerve tumor study and a collection of 10 cases where the combined use of clinic, neurophysiology and ultrasound guided the diagnostic process of nerve tumors. All the patients presented a clinic pattern of nerve involvement and everyone was evaluated with neurophysiology which confirmed a mononeuropathy, but without the possibility of a sure diagnosis. The following ultrasound evaluation allowed to visualize a focal lesion, compatible with a nerve tumor. These cases show that neurophysiology and ultrasound together contribute in diagnosis of peripheral nerve tumors. Ultrasonography is not able to certainly define the type of tumor, but it gives suggestions about discrimination between schwannoma and neurofibroma. Nerve ultrasound is useful in the assessment of peripheral nerve tumors.